Role of Local Government and MSMEs Performance: The Case of Ethiopia - Gamo, Kataro Galasso; Gollagari, Ramakrishna (International Journal of Small and Medium Enterprises, 2020)
Micro, small and medium enterprises (MSMEs) are one of the important sectors in both developed and developing countries contributing to economic growth and poverty alleviation. They play a significantly important role in contributing to economic growth, with a major share of employment in Ethiopia. However, in purposively selected three Urban Administrations under the study, the sectors are not playing their essentially expected roles. This study, therefore, examined the role of local government in supporting MSMEs performance. The study employed a mixed method approach using both quantitative and qualitative data. Data required for the study are gathered from secondary and primary sources. Secondary source data are gathered from books, journals, and related earlier research outputs as well as from the regional, zonal and administrative towns archival. Primary data are gathered from extensive field works through a questionnaire survey, key informant interviews, and personal observations by employing structured and unstructured questionnaires. The sample population is identified using stratified sampling design, thus, 541 samples are identified. Furthermore, 22 enterprise owners/managers were identified purposively as a target sample for key informant interviews. Document analysis, narrative analysis, and descriptive statistics have been used to analyze the data. The findings of the study indicated that, low level of employment and capital generation of MSMEs due to ineffective local government support. This study is important to attract investment and enhance the performance of the businesses in the local area. In general, this study will be significant to enhance the economic growth of the region by creating employment to reduce the heavy burden placed on larger cities by accommodating the ever-increasing population of the region. Therefore, local government institutions should create a conducive local business environment to attract more investment and promote the existing firms’ performance.